Effect of long-acting penicillin and Levamisole® on gain and health of stressed calves - Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two studies were conducted to determine the effect of long-acting penicillin and/or levamisole injected at arrival or levamisole injected on day 1 and/or day 7 on the health and gain of newly received, highly stressed, light weight calves. Levamisole injected at arrival reduced (P<.05) sickness of newly arrived calves during the first 5 days. However, it did not reduce overall sickness during the receiving period. Long-acting penicillin injected at arrival did not reduce sickness, but did improve (P<.05) gain of calves during the growing period. The combination of levamisole and long-acting penicillin or the combination of levamisole on day 1 and day 7 did not reduce morbidity in these highly stressed calves.
Keywords: Beef; Antibiotic; Levamisole; Penicillin; Anthelmintic; Stocker cattle